Simulation of geometrical parameters of Screen Printed Electrode (SPE) for electrochemical-based sensor - Roslan, Nurul Amira Farhana; Ab Rahim, Rosminazuin; Md Ralib @ Md Raghib, Aliza 'Aini; Za'bah, Nor Farahidah; Nordin, Anis Nurashikin; Bashri, Mohd Saiful Riza; Suhaimi, Muhammad Irsyad; Samsudin, Zambri; Ming, Lim Lai; Sugandi, Gandi (IEEE, 2021)
— Screen printing is a known method to produce disposable and low-cost sensors. Depending on the application such as food analysis, environmental health monitoring, disease detection and toxin detection, screen-printed electrodes can be fabricated in a variety of sizes and shapes. Modification of the electrode’s material and geometrical dimension may be done to produce effective screen-printed three-electrodes system. Thus, the effects of varying the working electrode (WE) area in radius of 0.9 mm to 2 mm, gap spacing between electrodes ranging from 0.5 mm to 1.6 mm, and the width of the counter electrode in range of 0.7 to 1.3 mm on sensor’s performance was investigated in this study through COMSOL simulation. It was found that the modification of the working electrode radius and the gap between the electrodes has the most significant effect on sensor’s performance, while modifying the width of the counter electrode (CE) shows no significant effect. Sensors with 0.9 mm radius or 2.54 mm² WE area and 0.5 mm gap spacing has shown the optimum performance with 0.026 A/m² current density which is contributed by 0.044 pF capacitance value. As a conclusion, regardless of the width of counter electrodes, a smaller gap between electrodes and a smaller working area would lead to optimal performance of a screen-printed three-electrode sensor system.